When women were dragons : a novel - Barnhill, Kelly Regan (Doubleday, 2022)
"Alex Green is a young girl in a world much like ours. But this version of 1950's America is characterized by a significant event: The Mass Dragoning of 1955, when hundreds of thousands of ordinary wives and mothers sprouted wings, scales and talons, left a trail of fiery destruction in their path, and took to the skies. Was it their choice? What will become of those left behind? Why did Alex's beloved Aunt Marla transform but her mother did not? Alex doesn't know. It's taboo to speak of. Forced into silence, Alex nevertheless must face the consequences of this disturbing event: a mother more protective than ever; a father growing increasingly distant; the upsetting insistence that her aunt never even existed; and helping to raise a beloved younger girl obsessed with dragons far beyond propriety. In this timely and timeless speculative novel, award-winning author Kelly Barnhill boldly explores rage, memory, and the forced limitations of girlhood. When Women Were Dragons exposes a world that wants to keep women small-their lives and their prospects-and examines what happens when they rise en masse and take up the space they deserve"--